Benefits Achieved by Applying Augmented Reality Technology in Marine Industry - S. Helle; S. Korhonen; A. Euranto; M. Kaustinen; O. Lahdenoja; T. Lehtonen (Germany, 2022)
In this paper we describe potential use cases of augmented reality technologies in marine industry.  In the two-year research project on-going at University of Turku we develop a mobile tool which enables visualizing 3D-CAD models and related information onto real environment and accessing data based on location in 3D-CAD model. The tool is designed to be used in industrial environment. The tool can be used to replace paper blueprints at the workplace and to increase efficiency in inspections, reviews, planning, reports and project plan follow-up. Potential use cases include for example documentation, virtual notes, inspections and installation checks. The research team has identified a number of use cases and analysed the benefits that can be achieved especially by applying augmented reality technologies. Finally, selected pilot use cases are described in detail.
COMPIT '14